Cashless stores and cash users - Oz Shy (Federal Reserve Bank of Atlanta, 2019)
The emergence of cashless stores has led several cities and states to ban such stores. This paper investigates this issue by characterizing consumers who pay cash for in-person purchases and consumers who do not have credit or debit cards. I construct a model of consumer payment choice and use data on payments to calibrate the burden imposed on consumers who do not have credit or debit cards from switching to cashless stores. The conclusion provides a discussion of alternatives to cash for in-person purchases that may be needed before all brick-and-mortar stores become cashless.
Keywords: D9; E42; 330; cashless stores; consumer payment choice; in-person purchases; alternatives to cash